Awareness and perceptions of electroconvulsive therapy among psychiatric patients: a cross-sectional survey from teaching hospitals in Karachi, Pakistan - Arshad, Mehreen (BioMed Central, 2007)
BACKGROUND: Electroconvulsive therapy (ECT) is shown to be effective in many psychiatric illnesses, but its distorted projection by the Pakistani media and its unregulated use by many physicians across the country have adversely affected its acceptability. Given this situation we aimed to assess the awareness and perceptions regarding ECT as a treatment modality among the psychiatric patients. METHODS: This was a questionnaire based cross-sectional study carried out at 2 tertiary care hospitals in Karachi, Pakistan. RESULTS: We interviewed 190 patients of which 140 were aware of ECT. The study showed that the level of education had a significant impact on the awareness of ECT (p = 0.009). The most common source of awareness was electronic and print media (38%), followed by relatives (24%) and doctors (23%). Physical injuries (42%) and neurological (12%) and cognitive disturbances (11%) were the commonly feared side effects. The most popular belief about ECT was that it was a treatment of last resort (56%). Thirty-nine percent thought that ECT could lead to severe mental and physical illness and 37% considered it inhumane. Patients' willingness to receive ECT was dependant on whether or not they were convinced of its safety (p = 0.001) and efficacy (p = 0.0001). CONCLUSION: We identified a serious lack of dissemination of information regarding ECT by the psychiatrists and the mental health care providers. This may be the result of an inadequate postgraduate training in Pakistan or just a lack of concern about the mentally ill patients. The media seemed to be the major source of information for our patients. We also saw the prevalence of a variety of myths regarding ECT in our society, which we feel may be responsible for the patients' adverse attitudes. Given the widespread applicability of ECT there is a dire need to dispel these misconceptions and improve its acceptability.